Cholinesterase activities and behavioral changes in Hypsiboas pulchellus (Anura: Hylidae) tadpoles exposed to glufosinate ammonium herbicide - Peltzer, Paola (2013)
In this study, amphibian tadpoles of Hypsiboas pulchellus were exposed to herbicide Liberty®, which contains glufosinate ammonium (GLA), for 48 h to the following concentrations: 0 (control), 3.55, 4.74, 6.32, 8.43, 11.25, 15, 20, 26.6, and 35.5 mg GLA L−1. Acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) activities, as well as swimming capabilities (swimming speed and mean distance) were measured in tadpoles whose concentrations displayed survival rates >85 %. Our results reveal that sublethal concentrations of GLA significantly inhibited both AChE and BChE activities in tadpoles with respect to the control, showing a concentration-dependent inhibitory effect. The highest inhibition percentages of AChE (50.86 %) and BChE (53.02 %) were registered in tadpoles exposed to 15 mg GLA L−1. At this concentration, a significant increase of the swimming speed and mean distance were found in exposed tadpoles with respect to the control, as well as a negative and significant correlation between swimming speed and BChE activity, thus suggesting that this enzyme inhibition is related to an increase in swimming speed. Therefore, exposure of tadpoles to GLA in the wild at concentrations similar to those tested here may have adverse consequences at population level because neurotransmission and swimming performance are essential for tadpole performance and survival.